DANGER OF IMPROPER USE OF MATHEMATICAL RESULTS, FORMULAS AND SYMBOLS : TRIGONOMETRY - Das, S.C. (SCHOOL SCIENCE, 2013)
The mistakes appearing in mathematics textbooks may often lead to defective teaching. Some of these common mistakes are conceptual mistakes in solving problems, in the statement of mathematical formulas or in steps involved in derivations. Often, the teachers fall victim to these errors and incorrectly solve a problem in the class, say by improper use of a formula, theorem, etc. This, in turn, perpetuates wrong ideas among young children. The author has selected a few of such mistakes and errors in trigonometry at the higher secondary stage. These examples are based on first-hand experience of the author with textbooks and classroom teaching practices for many years. In this article he has cited many interesting examples to explain some of these errors and mistakes in the teaching of trigonometry.